Application of the abc curve in inventory management in a construction company - Siqueira, Rafaela Ribeiro; Melo, Iasmine Aléxia de Aquino; Kato, Ricardo Bentes (Brazilian Journal of Production Engineering, 2021)
The progressive increase in competitiveness, organizations are looking for ways to improve their processes in order to reduce costs. Thus, it is recommended to do a good planning that allows decision making for stock management. In this sense, the ABC curve is applied as a support tool for stock control, allowing managers to have a detailed view of the products. Therefore, this research aims to discuss the application of the ABC tool in a company that operates in the civil construction sector, located in the city of Marabá-PA. Visits were carried out at the company to understand the entire inventory management process, as well as unstructured interviews with the sector manager and the professional responsible for the warehouse. To deal with the problems found, the ABC classification tool was used, to define the prioritization of managerial actions on the items in stock and thus to know which items are of greater relevance. Therefore, the results obtained go against the theory proposed by Vilfredo Pareto, of stocks in the 80/20 system, and that class A items must have low stocks, while class C items must have high stocks. Through the tool, it was found if the following class A results have a high stock size, with 11,352, Class B of the 19,552 materials present in the warehouse, the items classified as C correspond to only 3,237 of the materials in stock. This applied tool brought real and concrete information about the company’s stock management process, thus supporting the understanding of stock for managers